A Systematic Review of the Effects of Second-Eye Cataract Surgery on Motor Function - Sheppard, William E. A.; McCarrick, Dane; Wilkie, Richard M.; Baraas, Rigmor C.; Coats, Rachel O. (Frontiers in Aging, 2022)
Cataract removal surgery is one of the most commonly performed surgical procedure in developed countries. The financial and staff resource cost that first-eye cataract surgery incurs, leads to restricted access to second-eye cataract surgery (SES) in some areas, including the UK. These restrictions have been imposed despite a lack of knowledge about the impact of not performing SES on visuo-motor function. To this end, a systematic literature review was carried out, with the aim of synthesising our present understanding of the effects of SES on motor function. Key terms were searched across four databases, PsycINFO, Medline, Web of Science, and CINAHL. Of the screened studies (K = 499) 13 met the eligibility criteria. The homogeneity between participants, study-design and outcome measures across these studies was not sufficient for meta-analyses and a narrative synthesis was carried out. The evidence from objective sources indicates a positive effect of SES on both mobility and fall rates, however, when considering self-report measures, the reduction in falls associated with SES becomes negligible. The evidence for any positive effect of SES on driving is also mixed, whereby SES was associated with improvements in simulated driving performance but was not associated with changes in driving behaviours measured through in vehicle monitoring. Self-report measures of driving performance also returned inconsistent results. Whilst SES appears to be associated with a general trend towards improved motor function, more evidence is needed to reach any firm conclusions and to best advise policy regarding access to SES in an ageing population.